(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article on the material M. Kropivnitskiy letters to his childhood friend E. Myachikov highlights some relevance to the middle of the XIX century. socio-political issues, which were later reflected in his dramaturgical work. Among them – the problems associated with the formation of peasant cooperatives in Ukraine, local authorities, Ukrainians discrimination on national origin, and more.